Postoperative pain relief by epidural local anesthetics or morphine and intramuscular tramadol HCl influence on the stress response to surgery - Onal, A. (My University, 1993)
[Abstract Not Available]
Keywords: bupivacaine; hydrocortisone; insulin; local anesthetic agent; morphine; tramadol; abdominal surgery; adult; article; clinical article; controlled study; human; intramuscular drug administration; male; postoperative pain; surgical stress